(untitled) (Sociologisk Forskning, 2019)
Cleaning is a practice with low status. Most people single out cleaning as the least attractive of household chores and the people who clean as a profession are usually badly payed. This article is an attempt to discuss why these practices have such a bad reputation – in everyday life, in work, in popular culture and, not the least, in the feminist movement. Through ethnographic data primarily based on interviews, I investigate the historically imbedded meanings tied to practices of tidying up. Drawing on theories of queer temporality, I highlight what I want to call the temporality of cleaning – the repetitiveness and direction backwards and sideways instead of forward – as a possible answer. The circular practice of taking care of our physical remains remind us of our approaching death, rather than of progress, and thus generates feelings of anger and despair. But instead of ignoring or avoiding this reminder of another time, I argue for a feminist appraisal of the temporality of cleaning.